Acupuncture Treatment with Dense–Disperse Mode Electrostimulator for Sciatica Patients at the BSA Depok Acupuncture Clinic - Amin Karyaman; Mayang Wulandari; Leny Candra Kurniawan; Chantika Mahadini (International Journal of Science and Environment (IJSE), 2026)
Sciatica is a lumbosacral radicular pain condition that often leads to functional limitations and decreased quality of life. Acupuncture with electrical stimulation is one of the non-pharmacological therapies used in the management of sciatica. The dense–disperse mode of electroacupuncture is reported to provide a more stable analgesic effect through alternating low- and high-frequency stimulation. This study aimed to describe the benefits of acupuncture care using dense–disperse electrical stimulation in reducing pain among sciatica patients at BSA Acupuncture Clinic, Depok. This study employed a descriptive design involving sciatica patients who received acupuncture therapy with dense–disperse electrical stimulation based on standard acupuncture protocols. Pain reduction was evaluated during the treatment period. The results indicated that acupuncture care with dense–disperse electrical stimulation contributed to improvement in pain complaints among sciatica patients. This therapy may serve as a safe and effective non-pharmacological alternative for pain management in sciatica cases in clinical acupuncture settings.